Time-scale and mechanism of subsidence at Lassen Volcanic Center, CA, from InSAR - Parker, Amy; Biggs, J.; Lu, Z. (Elservier, 2016)
Observations of volcanic subsidence have contributed to our understanding of the eruption cycle, hydrothermal systems and the formation of continental crust. Lassen Volcanic Center is one of two volcanoes in the southern Cascades known to have subsided in recent decades, but the onset, temporal evolution, and cause of subsidence remain unconstrained. Here we use multiple sets of InSAR data, each corrected using the North American Regional Reanalysis atmospheric model, to determine the temporal and spatial characteristics of deformation between 1992 and 2010. Throughout this period all datasets reveal subsidence of a broad, 30–40 km wide region at rates of ~ 10 mm/yr. Evaluating past geodetic studies we suggest that subsidence may have been ongoing since the 1980s, before which it is unlikely that significant ground deformation occurred. By combining multiple tracks of InSAR data we find that the ratio of horizontal to vertical displacements is high (up to 3:1), and source inversions favour a point source located at ~ 8 km depth. Time-series analysis suggests that the rate of volume change of this source may have varied over time. The source geometry and the temporal evolution of deformation contrasts to subsidence observed at nearby Medicine Lake Volcano since the 1950s. We evaluate possible causes of subsidence at Lassen Volcanic Center in light of tectonic setting and hydrothermal activity, and suggest that regional GPS measurements will be key to understanding the role of crustal extension plus other hydrothermal/magmatic processes in deformation during recent decades.